Osteochondroma of the mandibular condyle - Report of an atypical case and the importance of computed tomography - Neelam N. Andrade; Trupti M. Gandhewar; Prathmesh Kapoor; Roy Thomas (Elsevier, 2014)
Osteochondroma is a rare tumor of the mandibular condyle. Much confusion seems to exist in the literature in differentiating these tumors from chondromas as well as condylar hyperplasias.Due to considerable overlapping features between chondromas and condylar hyperplasia, it is likely to get misdiagnosed, thereby resulting in inadvertent errors in the treatment.A case report of a 35 year old male patient with mandibular deviation and malocclusion is presented here. He initially went unnoticed for features of an osteochondroma of the mandibular condyle but was subsequently treated for the same.